Review of Transport Tariff at Ferry Port on Track Kariangau– Penajam, East Kalimantan Province - Windi Nopriyanto; Sri Kartini; Deska Uliyani (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2019)
The Ferry Port is located in the Village Kariangau with geographical location 116˚ 49 '2.852